Legal Responsibility For Occupational Safety Of Parcel Delivery Courier Partners In Indonesia - Alfiaturrohmania, Ulil; Fidhayanti, Dwi (Legal Spirit, 2024)
The lives of courier partners in the package delivery industry in Indonesia are full of safety-threatening challenges, especially when they use the "Cash On Delivery" (COD) payment system. Courier partners are often intimidated and mistreated by some customers, often buyers do not want to pay for COD packages because they feel the package is not suitable or the delivery is late, they must also be faced with the risk of traffic accidents. Courier partners are also considered informal workers who do not have clear attachments to service provider companies or government agencies, which causes companies to not have clear guidelines for risk management in this matter. This research was conducted to find out how legal responsibility for the work safety of courier partners in Indonesia and to find out the challenges and risks experienced by courier partners when carrying out their work. The research method used in this research is normative juridical using a statutory approach. Primary and secondary legal materials were obtained through literature studies and analyzed using descriptive methods. The results showed that the law enforcement used to protect the work safety of courier partners is Law No. 1 of 1970 concerning work safety.